ISTILAH-ISTILAH KHUSUS DALAM CHATTING (Sebuah Analisis Sosiopragmatik) - Bambang Hariyanto (Sunan Kalijaga State Islamic University Yogyakarta, 2010)
This paper aims at describing the use of language on the internet, especially language terms in chatting. It is claimed that the language terms have an important role for the chatters to make interaction and relationship with each other for certain purposes. The important role of language can be seen from the fact that many chatters use different language styles and speech variations in chatting over the Internet Relay Chat (IRC). The model of IRC communication is a kind of communication media for communication (chatting) by using computer keyboard in writing symbols or